Penerapan Employer Branding Terhadap Kepuasan Kerja - Nazwa P.P., Jeihan; Irbayuni, Sulastri (LPPM Politeknik Piksi Ganesha, 2024)
Employer branding has a strategic role in building a positive image of a company, not only to attract the best talent, but also to increase employee job satisfaction. This article reviews the role of employer branding in the context of job satisfaction, through various human resource development programs that have been implemented by PT Victory International Futures. The article highlights that strong employer branding can increase a sense of belonging, strengthen loyalty, and create a more productive and collaborative work environment. Some of the factors in creating sustainable job satisfaction include career development programs and recognition of employee contributions. This dedication provides readers with insights to optimize employer branding strategies as part of efforts to improve employee well-being and organizational competitiveness.